Analisis Kualitas Pelayanan dalam Penerbitan Sertifikat Tanah di Badan Pertanahan Nasional Kabupaten Nagan Raya - Ikhwal Mauliza; Ilhamsyah, Fadhil; Hasanuddin, Hasanuddin (CV RIFAINSTITUT, 2021)
The purpose of this study is to analyze the quality of service in the issuance of land certificates at Badan Pertanahan Nasional (BPN) Nagan Raya Regency. This research is qualitative research with a post-positivist approach. In this study the data obtained by researchers from observations, interviews, and documentation. The results of this study note that the certainty of the time and method of service in the issuance of land certificates at the BPN Nagan Raya Regency is still not done well. This is because officers still often extend the process of making land certificates, then in terms of the cost of obtaining land title certificates at the Nagan Raya BPN office, there are still many people who feel dissatisfied because there are additional costs that must be met by the community such as transportation costs for officers. Then regarding the obstacles that are often encountered by officers in terms of issuing land certificates are the frequent occurrence of disputes or disputes over land, incomplete files in the management of land certificates, boundary stakes, and lack of timeliness. Therefore, it is expected that employees at the Nagan Raya Regency BPN Office can provide accurate explanations to the community when processing land certificates both in terms of completeness of files, costs and time required by employees, so that with this the community can feel good service and comfort. and employees can carry out their duties according to the tempo that has been given to the community.